The subjective norms of sustainable consumption: A cross-cultural exploration - Minton, Elizabeth A.; Spielmann, Nathalie; Kahle, Lynn R.; Kim, Chung-Hyun (Journal of business research, 2018)
Although extensive research has explored aspects of sustainable consumption, such as specific sustainable behaviors and motivations for participating in sustainable activities, little research has examined the role of national culture and how pragmatism influences sustainable consumption. Sustainable consumption can encompass both sustainable attitudes and sustainable behaviors, and in this research, two types of social norms related to sustainable consumption (normative and self-enhancing) are also included and examined across three nations (France, Japan, and US). The findings suggest that differences in consumption are explained, in part, by the country's level of pragmatism, a cultural value (Hofstede, 1991). Building off the theory of reasoned action, findings also show that sustainable attitudes mediate the relationship between the level of pragmatism of a respondent's nation and sustainable behaviors.